Phylogenetic relationships in the cricket tribe Xenogryllini (Orthoptera, Gryllidae, Eneopterinae) and description of the Indian genus Indigryllus gen. nov. - Jaiswara, R. (Wiley Online Library, 2019)
The subfamily Eneopterinae is known greatly for its diversified acoustic modalities and disjunct distribution. Within Eneopterinae, tribe Lebinthini is the most studied group, due to its highest species diversity (ca. 150 species in 12 genera), endemic distribution on the islands of Southeast Asia and of the South West Pacific, males’ ability to produce high‐frequency calling songs, and evolution of females’ vibrational response. To investigate the distribution pattern and diversification of acoustic and behavioral attributes in a larger frame, clear understanding of phylogenetic relationships within other tribes of Eneopterinae is vital. In this study, we focus on the tribe Xenogryllini, sister group of Lebinthini. Xenogryllini, as opposed to Lebinthini, is known by fewer species (11 species in two genera), distributed widely in continental Asia and Africa, and for producing low‐frequency calling songs. We describe a new genus Indigryllus with a new species of the tribe Xenogryllini, discovered from the southwest of India. We used eight molecular genetic markers to reconstruct the phylogenetic relationships. The resultant phylogenetic tree is used to compare and discuss distribution patterns and acoustic modalities between Lebinthini and Xenogryllini.
Only IISERM authors are available in the record.
Keywords: Biogeography; Lebinthini; Pseudolebinthus; Systematics